Assessing frailty amongst older people admitted to hospital in a low-income setting: a multicentre study in northern Tanzania - Sean L Davidson; Luke Emmence; Sara May Motraghi-Nobes; Emily Bickerstaff; George Rayers; Godrule Lyimo; Joseph Kilasara; Mary Chuwa; Fortunatus Kisheo; Elibariki Kisaruni; Sarah Urasa; Emma Mitchell; et al. (BMC Geriatrics, 2024)
Abstract Background Populations are ageing globally and Low- and Middle-Income Countries (LMICs) are experiencing the fastest rates of demographic change. Few studies have explored the burden of frailty amongst older people in hospital in LMICs, where healthcare services are having to rapidly adapt to align with the needs of older people. This study aimed to measure the prevalence of frailty amongst older people admitted to hospital in Tanzania and to explore their demographic and clinical characteristics. Methods This study had a prospective observational design. Over a six-month period, all adults ≥ 60 years old admitted to medical wards in four hospitals in northern Tanzania were invited to participate. They were screened for frailty using the Clinical Frailty Scale (CFS) and the Frailty Phenotype (FP). Demographic and clinical characteristics of interest were recorded in a structured questionnaire. These included the Barthel Index, the Identification of Elderly Africans Instrumental Activities of Daily Living (IADEA-IADL) and Cognitive (IDEA-Cog) screens, the EURO-D depression scale and Confusion Assessment Method. Results 540 adults aged ≥ 60 were admitted, and 308 completed assessment. Frailty was present in 66.6% using the CFS and participants with frailty were significantly older, with lower levels of education and literacy, greater disability, greater comorbidity, poorer cognition and higher levels of delirium. Using the FP, 57.0% of participants were classed as frail though a majority of participants (n = 159, 51.6%) could not be classified due to a high proportion of missing data. Conclusions This study indicates that the prevalence of frailty on medical wards in northern Tanzania is high according to the CFS. However, the challenges in operationalising the FP in this setting highlight the need for future work to adapt frailty screening tools for an African context. Future investigations should also seek to correlate frailty status with long-term clinical outcomes after admission in this setting.